2013
DOI: 10.7705/biomedica.v33i3.1534
|View full text |Cite
|
Sign up to set email alerts
|

Estado de la susceptibilidad a insecticidas de uso en salud pública en poblaciones naturales de Aedes aegypti (Diptera: Culicidae) del departamento de Casanare, Colombia

Abstract: It appears that the P450 may play an important role in resistance to pyrethroids and DDT, still other resistance mechanisms may be acting in populations. Susceptibility to organophosphate allows continued use of this chemical group to interrupt transmission of dengue in Casanare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
3
20
0
2
Order By: Relevance
“…On the other hand, the susceptibility test with the organophosphate malathion showed that the "Moniquirá" strain was susceptible to this insecticide. Similar results have been reported in the departments of Antioquia, Putumayo, Chocó, Nariño, Cauca, Atlántico, Casanare, and Caldas [8,16,26,27,29]. However, losses of susceptibility to this insecticide attributed to its intensive use have been reported in Colombia and other countries of the continent [8,31,32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the susceptibility test with the organophosphate malathion showed that the "Moniquirá" strain was susceptible to this insecticide. Similar results have been reported in the departments of Antioquia, Putumayo, Chocó, Nariño, Cauca, Atlántico, Casanare, and Caldas [8,16,26,27,29]. However, losses of susceptibility to this insecticide attributed to its intensive use have been reported in Colombia and other countries of the continent [8,31,32].…”
Section: Discussionsupporting
confidence: 82%
“…Similar results have been reported in other Colombian regions [8-10, 16, 26, 27]. This generalized state of loss of susceptibility to this insecticide in the country has been mainly related to (i) metabolic resistance due to the increase in the activity of detoxification enzymes [8,9,16,[27][28][29]; (ii) Cross-resistance with organophosphates by high selection pressure with temephos which has been widely and intensively used in the country [8,16,28], and (iii) presence of kdr mutations by pyrethroid selection pressure used both institutional level as community [10][11][12]. It is possible that the loss of susceptibility to lambda-cyhalothrin reported in this work, is related to the prolonged use, during ten years, of organophosphate and pyrethroids in the department of Boyacá for the control of A. aegypti and triatomines (Personal communication of health local secretary, Boyacá).…”
Section: Discussionsupporting
confidence: 80%
“…Our findings of resistance to permethrin were consistent with those reported by Maestre et al [13] for Barranquilla and Montería; however, for Cartagena and Valledupar, Maestre et al had previously reported susceptibility, while we observed resistance using the WHO bioassay but susceptibility using the CDC bioassay. For this same insecticide Ardila et al [12] encountered resistance in the department of Casanare, as did Fonseca et al [10] in the departments of Chocó Antioquia and Putumayo using both bioassay methodologies. The results of the intensity bioassays for both permethrin and λ-cyhalothrin for the populations that had shown resistance using the CDC methodology resulted in 100% mortality when the diagnostic dose was doubled, suggesting that while resistance was present in the populations, it had not yet reached a high level of intensity.…”
Section: Plos Onementioning
confidence: 83%
“…The findings demonstrate variability in susceptibility to the insecticides temephos, λ-cyhalothrin, deltamethrin, permethrin, cyfluthrin, etofenprox, malathion, fenitrothion, pirimiphos-methyl, bendiocarb, and propoxur [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Moreover, increased activity levels of insecticide-degrading enzymes, such as nonspecific esterases, mixed-function oxidases (MFOs), glutathione S-transferases (GSTs), and insensitive acetylcholinesterase (iAChE), have been observed in resistant populations [9][10][11][12][13]24]. In addition, the kdr mutations V1016I [13,30], F1534C [31], and V410L [15] associated with pyrethroid resistance have recently been detected.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation